The Influence of Work Discipline Motivation and Work Facilities on the performance of teachers in secondary schools Upper/Vocational Major General Sutoyo SM - Putri, Tiara Hastina; Anwar, Yohny; Malikhah, Ikhah (Journal of Community Research and Service, 2024)
This research was conducted at SMU/SMK Mayjend Sutoyo with the aim of analyzing the influence of work motivation, work discipline and work facilities partially and simultaneously on the performance of teachers working at the school. The research population is 40 teachers who work as teachers in schools and the sample used is a saturated sample so the total research sample is 40 respondents. The types of data used are primary and secondary data, data collection techniques using literature studies, surveys and observations. Data analysis techniques are multiple linear regression, classical assumption testing and hypothesis testing. The research results show that work motivation, work discipline and work facilities partially and simultaneously have a positive and significant effect on teacher performance at SMU/SMK Mayjend Sutoyo. There is a strong correlation between work motivation, work discipline and work facilities with employee performance at SMU/SMK Mayend Sutoyo. Teacher performance can be explained by work motivation, work discipline and work facilities amounting to 48.9% and the remaining 51.1% can be explained by other variables not studied such as training, promotion, incentives, career development and so on.